High heat - Castle, Richard; Copyright Paperback Collection (Library of Congress) (Los Angeles, California, USA : Kingswell, 2017)
"An ISIS-style beheading of a journalist, carried out by a New York City group pledging fealty to that rogue state, becomes more than just another case for NYPD Captain Nikki Heat when the killers announce their next target: her husband, magazine writer Jameson Rook. Meanwhile, Heat is haunted by a fleeting glimpse of someone she swears is her mother ... a woman who has been dead for nearly twenty years"--
JHS
Text in English
Keywords: Heat, Nikki -- (Fictitious character) -- Fiction; Police -- New York (State) -- New York -- Fiction; Journalists -- Fiction; Beheading -- Fiction; New York (N.Y.) -- Fiction; Mystery fiction